Did Sarah Know? Unveiling the Isaac's Sacrifice - Eppang, Paulus; Sugihyono, Sugihyono; Hariyanto, Hariyanto; Winanto, Oey Natanael (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
This study investigates the question of whether Sarah was aware of God’s command to Abraham to sacrifice their son, Isaac. Although Genesis 22 does not explicitly mention Sarah’s awareness, this paper argues that the emotional, spiritual, and practical unity between Abraham and Sarah—consistently depicted throughout the biblical narrative—strongly implies her knowledge and joint participation. The account of Abraham and Sarah’s extensive spiritual journey, beginning in Mesopotamia, continuing through Haran, and culminating in Canaan, is reexamined through a close textual reading and contextual interpretation. Methodologically, the study employs a qualitative approach, utilizing hermeneutical analysis and Hebrew narrative criticism to interpret the biblical text and uncover the dynamics of the events described. The finding suggest that Abraham indeed informed Sarah, and that she knowingly shared in both the suffering and the faith required to endure this divine test alongside him.